Preparation and Evaluation of Gastroretentive Floating Pellets of Metronidazole (Bangladesh Pharmaceutical Journal, 2013)
Traditionally metronidazole is used in the treatment of bacterial vaginosis, trichomoniasis, amoebiasis and is also used in combination with other drugs to treat Helicobacter pylori (H. pylori) that causes stomach or intestinal ulcers. The main aim of this study was to develop a gastroretentive floating pellets for the treatment of above pathological conditions. Such kind of dosage form may provide an extension of drug presence in the upper GI tract resulting enhanced absorption and improved bioavailability for the treatment against protozoa and bacteria. Nine formulations of metronidazole floating pellets such as F1, F2, F3, F4, F5, F6, F7, F8 and F9 were prepared by ionic gelation method using different quantities of sodium alginate and psyllium husk. The drug and polymer ratio were 1:1.4, 1:1.5, 1:1.6, 1:1.6; 1:1.7, 1:1.8, 1:1.8, 1:1.9 and 1:2.0, respectively. The in vitro drug release study was carried out in 900 ml phosphate buffer (pH 7.4) at 37±0.50C and 50 rpm for 12 hours using USP XXIV paddle method and the content of drug release was determined by UV spectrometer at 277nm. Maximum and minimum drug release were found in F1 (88.63%) and in F6 (73.21%), respectively. It indicates that increase in sodium alginate concentration decreases drug release. All the formulations were buoyant for more than 12 hours in simulated gastric fluid at 370C. The maximum and minimum bulk density tapped were 0.57 and 0.52 in F1 and F9, respectively where drug loading were 14.07% in F1 and 12.56% in F9 which indicates that bulk density of the pellets is directly proportional to drug loading. The maximum and minimum swelling were in F3 (75%) and F7 (59%), respectively which demonstrate that swelling of pellets were inversely proportional to the sodium alginate concentration but it is directly proportional to psyllium husk content. In addition, the psyllium husk keeps the GI tract healthy by scavenging toxins and residues of digestive systems. Therefore, it can be concluded that combination of sodium alginate and biodegradable psyllium husk can be prospectively used for the preparation of gastroretentive floating pellets. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14504 Bangladesh Pharmaceutical Journal 16(1): 107-115, 2013